PP.20.33: CENTRAL BLOOD PRESSURE. (June 2015) - Tandurella, N.; Agostinis, M.; Tavecchia, L.; Mongiardi, C.; Moretti, S.; Gadaleta, C.; Ferrari, V.; Guasti, L.; Bertolini, A.; Grandi, A.M.; Maresca, A.M.
Abstract : Objective: Many cross-sectional studies have showed that central blood pressure (CBP), measured by applanation tonometry (AT) appears better related to target organ damage (TOD) than ambulatory blood pressure (ABP). The objective of this longitudinal study was to evaluate the association between changes in CBP and subclinical TOD in mild hypertensive patients. Design and method: We enrolled 30 patients (mean age 45.2 ± 6.8, 60% males) affected by mild hypertension (HT) without cardiovascular diseases or diabetes, never treated with antihypertensive drugs and 30 control subjects (NT) matched for age, gender and body mass index (BMI). For every subject, at baseline and at 3-year follow-up, we measured office blood pressure (OBP), ABP by 24-hour blood pressure monitoring, CBP and pulse wave velocity (PWV) by applanation tonometry; we also obtained anthropometric, metabolic, inflammatory, echocardiographic and carotid parameters. During the 3 years of follow-up, almost 60% of patients started antihypertensive drugs, according to their general practitioner. Results: During the 3 years of follow-up, HT showed a reduction in systolic and diastolic ABP (-6 ± 9 /−4 ± 6 mmHg, p = 0.001 / 0.001) and CBP (−6 ± 15 / −5 ± 11 mmHg, p = 0.021 / 0.007) while NT had no significant changes of these parameters. Indexed left ventricular mass (LVM) and carotid intima-media thickness (IMT) showed a reduction in HT (LVM: −3 (−5; −1) g/m2.7 p = 0.017; IMT: −0.13 (−0.16; −0.10) mm, p = 0.001) while in NT such parameters showed no significant changes. ABP was significantly correlated to LVM (SBP: r = 0.263; p = 0.042 PP: r = 0.388; p = 0.002) and PWV (SBP: r = 0.263, p = 0.043; DBP: r = 0.260, p = 0.045), while CBP was not associated to variations of the same parameters. Conclusions: In this longitudinal study CBP appears not related to changes in LVM and PWV, while ABP correlated to changes in LVM and PWV. In our study ABP but not CBP predicts variations of subclinical cardiac and vascular TOD in mild hypertensive patients.